EVALUATING AND IMPROVING THE PERFORMANCE OF COLD ASPHALT EMULSION MIXES - I Nyoman Arya Thanaya (Civil Engineering Dimension, 2007)
This paper describes investigation on the performances of cold asphalt emulsion mixes (CAEMs). The type of emulsion used was a cationic asphalt emulsion. The investigation was carried out at Leeds University, United Kingdom (UK). The objective of the experiments was to evaluate and to improve the performances of cold mixes and compared with hot mixes. For optimising the performances of the cold mixes, a target porosity of five to ten percent and indirect tensile stiffness modulus (ITSM) value of 2000 MPa was selected, suitable for low to medium trafficked roads. A simplified mix design procedure was used for producing the cold mixes. It was found that when properly designed, at full curing conditions, the stiffness (ITSM) of CAEMs were found to be very comparable to those of hot mixes. Test results also show that the addition of cement in the amount of one to two percent by mass of aggregates significantly improved the mechanical performance of cold asphalt mixes.